EFFECTS OF PANDEMIC COVID-19 ON THE MALAYSIAN ECONOMY, FOCUSED ON FIVE IMPORTANT INDUSTRIES AND SHARIAH VIEWPOINTS - MUHAMMAD HAIQAL TAJUDEN; MUHAMMAD NABIL NORHASMY; MUHAMMAD RIZWAN NASUTION BIN MOHD IDRIS; MUHAMMAD ADHAM MOHAMAD ARES; MUHAMMAD FAIZZUWAN MUSTAFA; FUADAH JOHARI (UIN Mataram, 2022)
Globally, more than 4.3 million confirmed cases and more than 2,90,000 fatalities occurred due to the COVID-19 disease outbreak, which profoundly affected the entire planet. This has also fanned fears of a forthcoming economic collapse and recession. This type of event is referred to as a